Quality Assessment of Hydroxychloroquine Tablet: A Comparative Evaluation of Drug Produced by Different Pharmaceutical Companies in Bangladesh - Md. Raihanur Islam; Md. Sakhawat Hossain; Md. Sanower Hossain; Mohammad Touhidul Islam; Sharifa Sultana; Nisarat Nijhum; Kutub Uddin Ahamed; Chee-Yan Choo; Ching Siang Tan; Khang Wen Goh (Progress in Microbes and Molecular Biology)
Hydroxychloroquine is the most commonly prescribed antimalarial extensively used to treat rheumatoid arthritis. It is extensively utilized as a repurposing drug, as well, in many countries worldwide to treat COVID-19. The pharmaceutical sector of Bangladesh is much enriched, and different pharmaceutical companies in Bangladesh produce this drug. Since the drug quality might vary significantly among different brands, assuring the quality of medicine is absolutely necessary considering the health issues, particularly therapeutic efficacy and safety. Therefore, this study examined the quality of hydroxychloroquine produced by Bangladeshi pharmaceutical companies, concentrating on quality control parameters: the assay, dissolution, disintegration, hardness, friability, and weight fluctuation. All the brands of hydroxychloroquine tablets contained the stated amount of API between the range of 96.41±0.62 and 100.61±0.71 that met USP specification (100±5%). All brands met the pharmacopeial limit for the percentage of weight fluctuation, hardness test, friability, and disintegration time. Weight variation was between 0.31±0.01% and 0.46±0.02%, hardness was between 4.31 ± 0.88 and 7.36 ± 0.74 kgf, friability was less than 1%, and disintegration time was 5.42± 0.11 and 5.42± 0.11 min. In the dissolution test, all the samples attained more than 70% dissolution after 30 minutes. The mean percentage of hydroxychloroquine released in phosphate buffer was between 95.44±0.55 (Brand B) and 98.19±0.39 (Brand C) after 60 min. No significant difference was among the tested drugs from different companies, and all quality assessment parameters were within USP specifications. Therefore, hydroxychloroquine from the Bangladesh market is safe and effective.